Hyperspectral imaging of irregular-shaped black microplastics in water - Gebejes Ana; Mubarak Hafiz Ramzan; Semenov Dmitri; Koistinen Arto; Peiponen Kai-Erik; Roussey Matthieu (EPJ Web of Conferences)
We utilize hyperspectral imaging (HSI) technique for detecting and characterizing black microplastics (BMPs) in water samples directly. We fabricated nine BMP samples from common daily life plastics using a metal work file with a diameter of approximately 200 mm. We discovered that, regardless of all these samples appearing black to the human eye, different BMPs have distinct spectral profiles observable in the visible, and near-infrared regions. Furthermore, we explored the impact of varying BMP quantities in the water samples and found that the reflectance of black microplastics may be influenced by the quantity of BMPs present in the sample.